Linguistic performance of Students with Autism Spectrum Disorders, and the role of Digital Technologies - Stathopoulou, Agathi; Temekenidou, Maria; Driga, Anna Maria; Dimitriou, Eleni (Eximia, 2022)
This study examines the perceptions that language teachers have in secondary schools about the performance of students diagnosed with autism spectrum disorders (ASD) in language lessons. More specifically, it tries to illustrate the views of language teachers on the ability of students with high functionality, to respond to the objectives of the Language curriculum in secondary schools. The sample was forty-eight (48) language teachers, three of which were men and forty-five women teaching at secondary schools in the Attica Perfecture. The results of the research showed that the majority of the language teachers believed that students with ASD cannot respond adequately to the requirements of the Language curriculum. Additionally, they consider that students with ASD cannot successfully respond to the language assessment criteria set by the Institute of Educational Policy. According to the research questions, it is concluded that the education level of the language teachers is directly related to their views about the proficiency of the students with ASD to respond to the requirements of the curriculum. Research data also showed that due to the inherent deficits of the students with ASD, Language teaching includes many difficulties.